The glory and the dream a narrative history of America, 1932-1972 - Manchester, William 1922-2004. (Boston Little, 1974)
A popular history of the United States which encompasses politics, military history, economics, the lively arts, science, fads, fashion, social changes, sexual mores, and communications, with brief biographies of notable Americans--Cover.
Included in the Dean Bonifacio Salamanca Collection.
UCASM-1022 (UCASM001022)
Bibliography: p. [1337]-1346.
Keywords: United States -- History -- 1933-1945.; United States -- History -- 1945-.